2020
DOI: 10.1002/uog.20421
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of postmenopausal women with non‐atypical endometrial hyperplasia on endometrial sampling

Abstract: Objective To assess the long‐term outcome of postmenopausal women diagnosed with non‐atypical endometrial hyperplasia (NEH). Methods This was a retrospective study of women aged 55 or older who underwent endometrial sampling in our academic medical center between 1997 and 2008. Women who had a current or recent (< 2 years) histological diagnosis of NEH were included in the study group and were compared with those diagnosed with atrophic endometrium (AE). Outcome data were obtained until February 2018. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…A long-term study of postmenopausal women with NEH had higher rates of progression to type 1 endometrial cancer (8. 15.4%, P<0.0001), and future hysterectomy (34.3% vs. 9.6%, P<0.0001), compared to postmenopausal women with atrophic endometrium [28].…”
Section: Methodsmentioning
confidence: 90%
“…A long-term study of postmenopausal women with NEH had higher rates of progression to type 1 endometrial cancer (8. 15.4%, P<0.0001), and future hysterectomy (34.3% vs. 9.6%, P<0.0001), compared to postmenopausal women with atrophic endometrium [28].…”
Section: Methodsmentioning
confidence: 90%
“…1 EH is a frequent cause of abnormal uterine bleeding and is believed to be a precursor of endometrial cancer (EC). 2,3 The revised World Health Organization classification divided EH into atypical endometrial hyperplasia (AEH) and nonatypical endometrial hyperplasia (NAEH) based on the presence of cytological atypia. 4 Studies on AEH consistently reported high risk for the coexistence of EC or progression to EC.…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial hyperplasia (EH) is a condition of excessive proliferation of the endometrium with an incidence of 133 per 100 000 woman‐years in the United States 1 . EH is a frequent cause of abnormal uterine bleeding and is believed to be a precursor of endometrial cancer (EC) 2,3 . The revised World Health Organization classification divided EH into atypical endometrial hyperplasia (AEH) and nonatypical endometrial hyperplasia (NAEH) based on the presence of cytological atypia 4 …”
Section: Introductionmentioning
confidence: 99%
“…ACOG recommends that endometrial sampling be performed in patients with AUB, who are older than 45, as a first-line test, which was one of the criteria in our study. [10][11][12][13][14][15][16][17][18] According to ACOG, in the case of younger than 45-year-old women, endometrial sampling should be performed only when a history of unopposed estrogen exposure exists e.g., PCOS, obesity, or failed management and persistent AUB. 19 In this study, the above guidelines were strictly followed when endometrial sampling was performed in younger than 45 subjects.…”
Section: Discussionmentioning
confidence: 99%